Eight weeks of different resistance training modes on big muscle hypertrophy of adolescents - and Sajeev Jos3, P.S. Sankaranarayanan1*, George Abraham2 (Journal of Experimental Sciences, 2011)
To investigate the eight weeks of different resistance training modes on big muscle hypertrophy of adolescents. Eighty physically active and interested students (N=80) were randomly selected as subjects and their age ranged between 14 and 17 years. The selected subjects were randomly divided into four equal groups with twenty subjects each (N=20). Group I was engaged with progressive resistance training (PRG), group II was given fluctuated resistance training (FRG), group III was given regressive resistance training (RRG) and group IV acted as control (CG). The experimental groups underwent their respective experimental programme for eight weeks 3 days per week and a session on each day. Control group was not involved with any specific training in addition to their activities. Thigh girth was taken as variable for this investigation. The pre and post test were conducted one day before and after the experimental treatment. Analysis of covariance (ANCOVA) was used to analyse the collected data. Scheffe’s test was applied as a post hoe test to determine which of the paired mean difference significantly. The results revealed that progressive, fluctuated and regressive resistance training (PRG, FRG and RRG) produced significant difference (p ≤ 0.05) on explosive power as compared to control group (CG). There was also significant difference (P≤ 0.05) between progressive and regressive resistance training groups (PRG & RRG) and fluctuated and regressive resistance training groups (FRG & RRG).